2022
DOI: 10.1039/d1qm01620b
|View full text |Cite|
|
Sign up to set email alerts
|

Recent advances in material design and reactor engineering for electrocatalytic ambient nitrogen fixation

Abstract: This review summarizes and discusses the recent efforts devoted to the material design and reactor engineering for electrocatalytic nitrogen reduction to ammonia under ambient conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 286 publications
(392 reference statements)
0
16
0
Order By: Relevance
“…It has been shown that some noble-metal based catalysts, transition-metal compounds and metal-free materials have achieved encouraging progress. 16,[27][28][29][30][31][32][33] For example, palladiumbased electrocatalysts can efficiently catalyze electrochemical NH 3 synthesis at a low overpotential, but the overall performances are far from satisfactory due to the weak interaction with N 2 and kinetic preference for the HER. 19,[34][35][36] The synergistic effect of metal alloy materials can effectively promote the electrocatalytic performance (such as PdCu, PdZn, PdPb, PdBi, AuPd, and others).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that some noble-metal based catalysts, transition-metal compounds and metal-free materials have achieved encouraging progress. 16,[27][28][29][30][31][32][33] For example, palladiumbased electrocatalysts can efficiently catalyze electrochemical NH 3 synthesis at a low overpotential, but the overall performances are far from satisfactory due to the weak interaction with N 2 and kinetic preference for the HER. 19,[34][35][36] The synergistic effect of metal alloy materials can effectively promote the electrocatalytic performance (such as PdCu, PdZn, PdPb, PdBi, AuPd, and others).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the introduction of vacancies or heteroatomic doping, the construction of specific structures, the exposure of active crystal planes, the construction of novel heterointerfaces and the single-atom strategies are considered to be effective ways to promote the intrinsic and/or apparent activity. 9,28,29,[39][40][41][42][43] More specifically, a reasonable construction of defect sites with a unique coordination environment and special electronic structure in nanomaterials as active sites for N 2 adsorption and activation has been widely concerned and studied, which is regarded as an effective means of designing efficient NRR electrocatalysts. 44,45 Then, whether N 2 enrichment and activation and further electrocatalytic reduction can be achieved through rational construction of defect sites and coupling metal active sites of the alloy catalyst, and tuning the unsaturated coordination and electronic structure, is still a scientific issue worth exploring.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, seeking an effective and feasible technology for its removal is a challenging topic. Photocatalysis provides a way to remove air pollutants (e.g., NOx) by installing catalysts either inside the exhaust pipe or on the road surface [ 1 ]. As a typical photocatalyst, g-C 3 N 4 -based materials are also widely investigated in this aspect.…”
Section: Applications Of G-c 3 N 4 ...mentioning
confidence: 99%
“…With the development of economies and the growth of populations, pressures on energy demand and environmental pollution continue to increase all over the world [ 1 , 2 , 3 , 4 ]. Fossil fuels, which currently account for a large amount of the world’s energy, are increasingly consumed, resulting in negative impacts on the environment through the release of CO 2 , which is a serious greenhouse gas.…”
Section: Introductionmentioning
confidence: 99%
“…Electrochemically advanced oxidation processes can be used to degrade organic pollutants into CO 2 , H 2 O, and inorganic small molecules by generating highly oxidizing reactive oxygen species, using a green and efficient process, free from secondary pollutants [ 17 , 18 ]. Brinzila et al [ 19 ] used boron-doped diamond electrodes to degrade tetracycline and found that it could be completely degraded after a 4 h reaction, even at high concentrations (>150 mg/L).…”
Section: Introductionmentioning
confidence: 99%